Training university students in obstacle course navigation during physical culture classes - Kolesnikov, N.V.; Antonov, A.V.; Prokhorenko, A.A.; Udalova, M.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to develop, through modelling, an obstacle course and implement it into the educational process for students of military conscription age. Methods and structure of the study. The article addresses issues related to preparing students for service in the Armed Forces of the Russian Federation. The following research methods were employed: literature review, data collection, and mathematical processing of research results. Results and conclusions. The incorporation of obstacle course activities into the educational process within the discipline “Elective Courses in Physical Education” for senior students not only promotes the development of their comprehensive motor activity but also builds applied skills and enhances their level of physical fitness.